Navigating Challenges in Remote Speaking Tasks: Unveiling Technical and Non-Technical Problems Faced by Students - Tauchid, Ahmad; Agung Barata, Mula; Wafa, Khoirul; Wijayanti, Riris (International Review of Research in Open and Distributed Learning, 2024)
In today’s digitally driven era marked by widespread remote communication, individuals grapple with diverse challenges when undertaking speaking tasks from a distance. Despite extensive research on communication dynamics in virtual contexts, the specific hurdles associated with remote speaking tasks remain understudied. This research addresses this gap by qualitatively exploring the complexities of such challenges and proposing practical strategies for effective communication in virtual environments. Employing a qualitative research approach, a survey with open-ended questions was administered to 19 students in the English Education program, and NVivo 12 was used for analysis. The findings highlight technical and non-technical challenges in remote speaking tasks, emphasizing the critical role of digital proficiency and a stable technical infrastructure. The study underscores the need to address personal and social aspects, suggesting solutions that encompass a precise and adaptive approach, including ensuring a reliable Internet connection, strategic use of digital resources, enhancement of technical skills, and a holistic strategy to tackle both technical and non-technical challenges. This research implies that educators should prioritize developing students’ digital proficiency and adopt a comprehensive approach that tackles both technical and psychological challenges, aiming to boost confidence and interpersonal skills in virtual learning environments.